Effect of DMPPO, a phosphodiesterase type 5 inhibitor, on hypoxic pulmonary hypertension in rats - Eddahibi, Saadia (1998)
1. Cyclic guanosine 3′–5′-monophosphate (cyclic GMP) is the second messenger of important physiologically active mediators controlling the pulmonary vascular tone. To potentiate the effects of cyclic GMP on the pulmonary vasculature, we used DMPPO, a new selective PDE-5 inhibitor, and examined its action in a rat model of hypoxic pulmonary hypertension. 2. Levels of cyclic GMP measured during baseline conditions at 5 and 60 min of perfusion were similar in the perfusate of isolated lungs from normoxic and chronically hypoxic rats and did not differ with time. Pretreatment with DMPPO (1 μM) induced a larger increase in cyclic GMP concentration in the perfusate from chronically hypoxic rat lungs (319±36 at 5 min to 1821±83 pmol ml(−1) at 60 min) than in normoxic rat lungs (329±20 to 1281±127 pmol ml(−1), P<0.05). 3. In isolated lungs preconstricted with U-46619, pretreatment with DMPPO (1 μM) potentiated the vasodilator effects of atrial natriuretic peptide (100 pM–10 nM) and sodium nitroprusside (1 pM–10 nM), but did not alter vasodilation to isoproterenol. 4. In conscious rats previously exposed to 15 days hypoxia and studied under 10% O(2), DMPPO (0.01, 0.05 and 0.1 mg kg(−1), i.v. bolus) caused a dose-dependent decrease in pulmonary arterial pressure (Pap) with no change in systemic artery pressure (Sap) and cardiac output. 5. Continuous infusion of DMPPO (0.1 mg kg(−1) h(−1) i.v. by osmotic pumps) in rats exposed to 10% O(2) during 2-weeks reduced the Pap (P<0.05) and the degree of muscularization of pulmonary vessels at the alveolar wall (P<0.01) and alveolar duct levels (P<0.05) despite no significant change in right ventricular hypertrophy. 6. These results suggest that cyclic GMP phosphodiesterase inhibition may selectively dilate pulmonary circulation during chronic hypoxia.